2008
DOI: 10.1159/000142048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Safety, Risk Factors and Pretreatment Methods during Rush Hymenoptera Venom Immunotherapy

Abstract: Background: The safety profile of venom immunotherapy is a relevant issue. We evaluated the frequency of severe adverse events (SAE), associated risk factors, retrospective comparison of pretreatment protocols including solely H1 receptor blockers and a combination of H1 and H2 receptor blockers during rush Hymenoptera venom immunotherapy. Methods: The study group comprised 118 patients. The treatment was initiated according to a 5-day rush protocol with the use of standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
2
10
0
1
Order By: Relevance
“…VIT SRs occurred during the dose-increase phase at a median dose of 46 µg (range 2-100 µg), which is comparable to the EAACI study where the median dose in the dose-increase phase was 30 µg (range 0.01-150 µg), and the Polish study where the majority of SRs in the dose-increase phase developed at a dose of 40 µg or 60 µg of the venom extract [14,16].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…VIT SRs occurred during the dose-increase phase at a median dose of 46 µg (range 2-100 µg), which is comparable to the EAACI study where the median dose in the dose-increase phase was 30 µg (range 0.01-150 µg), and the Polish study where the majority of SRs in the dose-increase phase developed at a dose of 40 µg or 60 µg of the venom extract [14,16].…”
Section: Discussionsupporting
confidence: 70%
“…A Polish study observed SRs in 15.2% of patients during the 5-day rush induction phase of VIT, whereas severe adverse events were present in 5.9% patients. The risk factors were bee venom immunotherapy and female sex [16]. In a study in Spain it was concluded that immunotherapy is a safe treatment when EAACI guidelines are strictly followed [17].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment with antihistamines reduces the number and severity of large local reactions and mild systemic reactions such as urticaria and angio-edema. It is advised that antihistamines be administered 1 h before injection until the maintenance dose has been shown to be well tolerated [49]. Antihistamine pretreatment might also increase the efficacy of VIT [50].…”
Section: Safety Of Vitmentioning
confidence: 99%
“…Forty-two systemic reactions (0.6% of all injections) were documented in 39 patients (3.4%) [57]. On the other side, some studies involving fast venom immunotherapy regimens have found a lower incidence of systemic reaction than with conventional treatments [45], whereas the systemic reaction incidence was higher with other protocols [58].…”
Section: Risk Factors For Severe Adverse Eventsmentioning
confidence: 99%